THERAPEUTIC EFFICACY OF “PHAGOMAST” BACTERIOPHAGE PREPARATION FOR THE TREATMENT OF COWS’ SUBCLINICAL MASTITIS - Horiuk, Y. V. (Scientific Progress & Innovations, 2021)
The excessive use of antibiotics is the main problem at treatment of cow staphylococcal mastitis because of arising antibiotic resistance in pathogens, which necessitates searching for alternative decisions to treat bacterial infections, including the traditional treatment of mastitis. The results obtained earlier show the po-tential of phago-therapy in the treatment of cow mastitis and require their further checking by conducting studies in vivo. The purpose of the work was to study the therapeutic efficacy of using the developed “Phag-omast” bacteriophage preparation at treatment of cow subclinical mastitis. To conduct the investigation, two groups of cows were formed according to the principle of conventional analogues: the control (the animals were treated according to the standard schemes on farms using anti-mastitis preparations based on antibiot-ics) and the experimental group (the animals were administered “Phagomast” bacteriophage preparation). The control of therapeutic efficacy was made 5 days after the last administration of the preparation by de-termining the number of somatic cells and content of S. aureus. The determining of the number of somatic cells was conducted by the method of Prescotte-Brid. To determine the amount of S. Aureus, BD Baird-Parker Agar (HiMedia, India) was used. The incubation was conducted at a temperature of 37°С, and the results were assessed after 24-48 hours. As a result of the studies, it has been established that the treatment efficacy while using “Phagomast” preparation is not worse than after using antibiotics. The number of ud-der quarters that restored their functions made 92.1%, and S. aureus was not isolated at all in fresh milk after finishing the treatment. It has been found that 5 days after finishing the treatment, the content of somat-ic cells in milk decreased by 16.8 times, and the milk suitable for the majority of practical purposes corre-sponded to the requirements of 3662:2018 State Standard of Ukraine “Cow milk-the raw product. Technical conditions”. Thus, “Phagomast” preparation based on bacteriophages can be applied as an alternative to antibiotics at organic livestock farming for the treatment of cow subclinical staphylococcal mastitis.